2012
DOI: 10.1186/1475-2875-11-68
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure of genes encoding vaccine candidate antigens of Plasmodium vivax

Abstract: BackgroundA major concern in malaria vaccine development is genetic polymorphisms typically observed among Plasmodium isolates in different geographical areas across the world. Highly polymorphic regions have been observed in Plasmodium falciparum and Plasmodium vivax antigenic surface proteins such as Circumsporozoite protein (CSP), Duffy-binding protein (DBP), Merozoite surface protein-1 (MSP-1), Apical membrane antigen-1 (AMA-1) and Thrombospondin related anonymous protein (TRAP).MethodsGenetic variability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
26
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 62 publications
10
26
1
1
Order By: Relevance
“…Thus, locally, there can be low levels of genetic variation even though regional genetic diversity is high. Such patterns have also been reported for genes encoding antigens (Chenet et al 2012b). This model offers interesting perspectives in the context of malaria elimination.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Thus, locally, there can be low levels of genetic variation even though regional genetic diversity is high. Such patterns have also been reported for genes encoding antigens (Chenet et al 2012b). This model offers interesting perspectives in the context of malaria elimination.…”
Section: Discussionsupporting
confidence: 68%
“…While surveys of mitochondrial genomes have reported limited variation consistent with a recent introduction of this parasite to the New World (Cornejo and Escalante 2005; Mu et al 2005; Culleton et al 2011), many other studies have documented extensive microsatellite variation even within small geographical regions (Imwong et al 2007; Joy et al 2008; Karunaweera et al 2008; Rezende et al 2010; Van den Eede et al 2010). In contrast, studies on nuclear genes encoding antigens have shown low local diversity (Grynberg et al 2008; Chenet et al 2012b) but strong geographic structure (Chenet et al 2012b). Meanwhile, despite having small sample sizes, two recent studies of the nuclear genome of P. vivax have found that genomes sampled within the Americas are nearly as divergent from one another as they are from genomes sampled on other continents (Chan et al 2012; Neafsey et al 2012).…”
Section: Discussionmentioning
confidence: 97%
“…Recombinant proteins were produced using regions of Pv MSP1 and Pv CSP1. Both proteins have been previously studied for their immunogenicity properties, while representing potential vaccine targets [30]. …”
Section: Discussionmentioning
confidence: 99%
“…falciparum and P. vivax isolates (10)(11)(12)(13)(14)(15)(16)(17). The majority of P. vivax AMA-1 (PvAMA-1) polymorphisms are described in domain I (13)(14)(15), whereas domain II is more conserved, suggesting an important function (16,17).…”
mentioning
confidence: 99%
“…The majority of P. vivax AMA-1 (PvAMA-1) polymorphisms are described in domain I (13)(14)(15), whereas domain II is more conserved, suggesting an important function (16,17). A number of phase II clinical trials using recombinant proteins or viruses based on P. falciparum AMA-1 (PfAMA-1) have been performed to date (18)(19)(20)(21).…”
mentioning
confidence: 99%